GLOBAL TRENDS IN HUMAN RESOURCE ACCOUNTING THROUGH BIBLIOMETRIC ANALYSIS ON SCOPUS DATABASE - Dermawan, Wildan Dwi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This study aims to map the topic of human resource accounting using the Scopus database with a time span from 1972 to 2023. The keyword used